ASV (Amplicon Sequence Variant) taxonomic affiliation analysis of Cryptosporidium scrofarum species in pigs in the Vologda Region, the Northwestern Federal District of the Russian Federation - A. L. Kryazhev; A. S. Novikov (Российский паразитологический журнал)
The purpose of the research is isolation, identification, and analysis of ASV (Amplicon Sequence Variant) types of Cryptosporidia spp. in pigs in the Vologda Region of the Russian Federation.Materials and methods. The research has been conducted in the Russian Federation for the first time. The research was conducted on pig farms in the Vologda Region of the Northwestern Federal District of the Russian Federation from January to October 2023. Feces were taken from piglets of various age groups, as well as milking sows. The samples were studied using the equipment of the resource center “Genomic Technologies, Proteomics and Cell Biology” of ARRIAM. Species of the genus Cryptosporidia were identified in fecal samples using high-throughput sequencing of 18S rRNA gene fragment amplicon libraries as obtained from nested PCR followed by “denoising”, sequence combining, and restoring the original phylotypes (ASV, (Amplicon Sequence Variant)).Results and discussion. Cryptosporidia spp. species were identified in each age group studied. As a result of high-throughput sequencing of the libraries using the Illumina technology, 20 to 100 thousand nucleotide sequences (reads) were obtained for each sample after processing of which a total of 2,372 ASVs were identified. The analysis of the ASV taxonomic affiliation performed with phylogenetic analysis supplemented by an analysis using the blastn algorithm in the GenBank database showed that, in total, 10 ASVs were only present in all studied samples that had high similarity to sequences deposited in the GenBank as 18S rRNA gene fragments of Cryptosporidium scrofarum. Eight ASV types were unique and did not repeat from farm to farm. Probably, these sequences belong to local populations of C. scrofarum subspecies. Of interest is the discovery of a unique Cryptosporidium sequence of ASV8 type which is only 91.47% similar to the closest relative of the genus, which may indicate a rather distant taxonomic relationship. This type of nucleotide sequence can be further described as a new species. All identified unique ASV nucleotide sequences were deposited in GenBank.